KINERJA PENDAMPING PROGRAM KELUARGA HARAPAN (PKH) DALAM PERTEMUAN PENINGKATAN KEMAMPUAN KELUARGA (P2K2) DI KECAMATAN BOJONGSOANG KABUPATEN BANDUNG - Reiki Polo Brice Depari Depari; Teta Riasih; Rosilawati Rosilawati (Jurnal Ilmiah Perlindungan & Pemberdayaan Sosial,, 2023)
The performance of the Family Hope Program Facilitator is a determinant of the success of the Hope Family Program in improving the living standards of the beneficiary families in accessing health services, education, and improving social welfare. This study aims to describe empirically the description of the performance of the hopeful family program companion in Bojongsoang District, Bandung Regency based on the characteristics of the Beneficiary Families, Aspects of Quality of Work, Punctuality, Ability, and Communication. The method used in this study is a quantitative method. Sources of data used in this study are primary data sources and secondary data sources. The sampling technique in this study used a sampling area (cluster). Data collection techniques used are questionnaires and documentation studies. The measuring instrument used in this study is the Rating Scale, as well as the face validity test. The results showed that the performance of the Family Hope Program Facilitator in Bojongsoang District was included in the very good category in every aspect. However, there needs to be an increase in Knowledge, Ability, and Communication for PKH facilitators in Bojongsoang District. Based on this, the researcher proposes a program "Capacity Strengthening for Family Hope Program Facilitators in Bojongsoang Sub-district" which aims to improve the performance of hopeful family program facilitators in Bojongsoang District, Bandung Regency.